Groups with incidence condition for noncyclic subgroups - Polovitskii, Ya. D.; Chernikov, N. S.; Chechulin, V. L. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We give a description of groups with incidence condition for noncyclic subgroups to within minimal noncyclic subgroups. We present a complete constructive description of locally graded groups (in particular, arbitrary locally finite groups) satisfying this condition.